Towards the quest for transforming Old Testament scholarship : the impact of political and socio-economic crises on scholarship in Zimbabwe - Rugwiji, Temba (2014)
Political and socio-economic crises in Zimbabwe in recent years had a negative impact on the country's scholarship, forcing some scholars to relocate to other parts of the world, and others to utilise both domestic and regional platforms to voice their concerns. In spite of the relocation and the subsequent brain drain, publications in differing genres from Zimbabwean scholars became a force to reckon with. This essay argues, however, that Old Testament (hereafter OT) scholarship in itself has not been fully represented on both the domestic and regional platforms. This project poses and then responds to the following question: Who are the OT scholars in Zimbabwe and what do they write? First, this study examines both the "push" and the "pull" factors that caused the brain drain in Zimbabwe. Second, consequences that ensued as a result of the political and socio-economic crises are explored. Third, the essay engages the above question by analysing contributions of some Zimbabwean scholars in the last few years. Fourth, some educational reforms are articulated towards transforming OT scholarship in Zimbabwe. Fifth, this treatise concludes by exploring the relevance of OT scholarship to society.
Keywords: Education; Old Testament scholarship; Zimbabwe; Politics